Caricaturing culture in India : cartoons and history in the modern world - Khanduri, Ritu Gairola (Cambridge University Press, 2014)
"Caricaturing Culture in India is a highly original history of political cartoons in India. Drawing on the analysis of newspaper cartoons since the 1870s, archival research and interviews with prominent Indian cartoonists, this ambitious study combines historical narrative with ethnographic testimony to give a pioneering account of the role that cartoons have played over time in political communication, public discourse and the refraction of ideals central to the creation of the Indian postcolonial state. Maintaining that cartoons are more than illustrative representations of news, Ritu Gairola Khanduri uncovers the true potential of cartoons as a visual medium where memories jostle, history is imagined and lines of empathy are demarcated. Placing the argument within a wider context, this thought-provoking book highlights the history and power of print media in debates on free speech and democratic processes around the world, revealing why cartoons still matter today"--